Efektivitas Karbon Aktif Buah Bintaro dan Kulit Buah Nangka dalam Menurunkan Parameter Fe, Mn dan Cu - Oktavianto, Achmad Afandi; Amalia, Aussie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Due to its high cellulose content, Bintaro fruit and jackfruit peel can be used as activated carbon. The purpose of this study was to determine the activator and optimum contact time and determine the appropriate adsorption isotherm on activated carbon of Bintaro fruit and jackfruit peel in reducing Fe, Mn and Cu parameters. In this study, the sample water used well water in Surabaya City. The variations used in this study are activator variations and contact time. The activators used are HCl and H2SO4 for the contact time used are 30, 60, 90 and 120 minutes. From the results of the study, the optimum activator was HCl with a contact time of 120 minutes with the highest percentage removal of Fe content of 88.8% by jackfruit peel activated carbon. For Mn reduction, the optimum activator is H2SO4 with a contact time of 120 minutes on jackfruit peel activated carbon with the highest percentage removal of 89.2%. For Cu reduction, the most optimal activator is HCl with a contact time of 120 minutes on jackfruit peel activated carbon with the highest percentage removal of 90.9%. The type of adsorption isotherm in the reduction of Fe, Mn and Cu levels in this study as a whole follows the Freundlich isotherm equation.